Analisis Yuridis Terhadap Penerapan Pasal 146 KUHP dalam Kasus Demonstrasi Anarkis - Komaruz Zaman, Muhammad Asiq; Fathinudin, Muhammad (PT Elaborium Elevasi Indonesia, 2023)
This study analyzes the legal application of Article 170 of the Indonesian Penal Code (KUHP) in cases of anarchistic demonstrations. It focuses on the interpretation and implementation of the law in the context of collective violence during public protests. The research identifies key challenges in enforcing this article, particularly in proving individual involvement in violent acts within large crowds. Additionally, the study highlights the importance of balancing law enforcement with the protection of human rights, especially the right to free speech during demonstrations.This research uses a qualitative method with a normative legal approach, analyzing primary and secondary data sources, including laws, regulations, and court rulings. The findings reveal that although Article 170 KUHP is relevant for handling anarchistic demonstrations, its implementation faces challenges such as identifying perpetrators and balancing enforcement with human rights.